Innovation in Language Learning and Teaching The Case of the Middle East and North Africa - Reinders, Hayo; Coombe, Christine; Littlejohn, Andrew; Tafazoli, Dara (New Language Learning and Teaching Environments,, 2019)
This edited collection presents a study of innovation in teaching, learning, assessment and teacher development practices in the Middle East and North Africa (MENA). The thirteen research-based chapters in this collection examine recent innovations in English language teaching, drawing on classroom, administrative and learning experiences from seven of the countries in the region. The major trends analyzed across the volume include the language skills of reading and writing and the prevalence of technology and technology-enhanced instruction. It highlights that innovative teaching, learning and assessment practices that are now in place in virtually all levels of English language teaching and learning from primary school to university to adult education sectors, and reflects on possible ways forward for innovation in the field of ELT. This book will provide valuable insight for scholars of applied linguistics and practitioners working in language policy, .